Thiol-based redox signaling in the nitrogen-fixing symbiosis - Frendo, Pierre; Matamoros, Manuel A.; Alloing, Geneviève; Becana, Manuel (Frontiers in Plant Science, 2013)
In nitrogen poor soils legumes establish a symbiotic interaction with rhizobia that results in the formation of root nodules. These are unique plant organs where bacteria differentiate into bacteroids, which express the nitrogenase enzyme complex that reduces atmospheric N2 to ammonia. Nodule metabolism requires a tight control of the concentrations of reactive oxygen and nitrogen species (RONS) so that they can perform useful signaling roles while avoiding nitro-oxidative damage. In nodules a thiol-dependent regulatory network that senses, transmits and responds to redox changes is starting to be elucidated. A combination of enzymatic, immunological, pharmacological and molecular analyses has allowed to conclude that glutathione and its legume-specific homolog, homoglutathione, are abundant in meristematic and infected cells, their spatio-temporally distribution is correlated with the corresponding (homo)glutathione synthetase activities, and are crucial for nodule development and function. Glutathione is at high concentrations in the bacteroids and at moderate amounts in the mitochondria, cytosol and nuclei. Less information is available on other components of the network. The expression of multiple isoforms of glutathione peroxidases, peroxiredoxins, thioredoxins, glutaredoxins and NADPH-thioredoxin reductases has been detected in nodule cells using antibodies and proteomics. Peroxiredoxins and thioredoxins are essential to regulate and in some cases to detoxify RONS in nodules. Further research is necessary to clarify the regulation of the expression and activity of thiol redox-active proteins in response to abiotic, biotic and developmental cues, their interactions with do wnstream targets by disulfide-exchange reactions, and their participation in signaling cascades. The availability of mutants and transgenic lines will be crucial to facilitate systematic investigations into the function of the various proteins in the legume-rhizobial symbiosis.